(untitled) (Islas, 2026)
Introduction: This article presents an initial study of a recent phenomenon: the adaptations of Latin American audiovisual products produced and made in the United States, with the aim of analyzing the modifications that occur in these adaptations. Methods: A comparable parallel corpus was compiled, and two pairs were initially selected: El Secreto de sus Ojos / Secret in Their Eyes and Yo soy Betty, la fea / Ugly Betty. The analysis focused on modifications in events, characters, and contexts (geographical and social). Results: A global analysis was constructed, taking into account the market context in which the products are situated, as well as the ways in which the modifications involve historical, cultural, linguistic, and social issues. It was observed that the adaptors chose different paths when bringing the film and the telenovela to the U.S. market. Conclusions: The adapted film is constructed from an essentially American perspective, responding to the assumption that Hollywood cinema presents itself as universal. In contrast, the adapted series seeks to attract Latin American audiences to U.S. television. A “Latina” protagonist is maintained, but American values are incorporated into the narrative.